The Correlation Between Workload And Occupational Stress Of Nurses In The Emergency Department Of Regional Public Hospital Rsud Prof. Dr. W. Z. Johannes Kupang - Antonius Rino Vanchapo; Serly Sani Mahoklory; Ni Made Merlin (Alma Ata University Press, 2019)
The emergency department in a hospital tends to pose a high stress level. This is due to the conditions, i.e., life-threatening condition of patients that often trigger the stress on the nurses. The nurses are required to act immediately and to possess specific skills to provide accurate treatment to the patients. Such a condition signifies the major role of nurses in a hospital. It also demands improvement in the performances of the nurses to conceptualize quality health services. Occupational stress is a term used to refer to depression or emotion, being irritable towards the situation of the workplace, and it is signified by both mental and physical condition of a person. This inevitably affects one’s health as and the spiritual condition. Excessive workload is among the factors causing occupational stress. This study aims at exploring the correlation between workload and occupational stress of nurses in the emergency department of Regional Public Hospital RSUD. Prof. Dr. W. Z. Johannes Kupang. The cross-sectional study involved 40 respondents selected using a total sampling method. The data were analyzed using the Pearson chi-square correlation. It is revealed that the p-value 0.000 is lower than α 0.05, meaning that H0 is rejected and signifying that workload correlates with the occupational stress of the nurses in the research site.